Analysis of Corporate Income Tax Reduction A Study Case on Manufacturing Companies in Indonesia in The Year 2008-2014 - Setyaningrum, Candra Dwi; Suryarini, Trisni (Jurnal Dinamika Akuntansi, 2016)
This research aimed to determine the effect of ABTD (Abnormal Book-Tax Differences) before and after tax rate reduction. This research also examined the effect of taxation facility, foreign operation, pretax cash flow from operation, and size of the company towards ABTD. Samples in this research are manufacturing company that listed in Indonesia Stock Exchange 2008-2014 by using method of purposive sampling so there are 357 companies. This research used multiple regression analysis. The result of this research indicates that the foreign operation variable and pretax cash flow from operation variable have positive effect on ABTD. While the size of the company variable has negative effect on ABTD. The conclusions of this research are that tax management depends on foreign operation, and earnings management depends on pretax cash flow from operation and size of the company.